P58 Economic evaluation of the GORE® VIATORR® stent in patients with complications of severe cirrhosis – ascites and bleeding: a UK cost-utility analysis. (28th September 2020) - Tripathi, Dhiraj; O'Neill, Frank; Patch, David; Joseph, Andrew; Aithal, Guru
Abstract : Introduction: Variceal bleeding and refractory ascites are common clinical manifestations of liver cirrhosis. Transjugular intrahepatic portosystemic stent-shunt (TIPSS) procedures can increase survival and improve quality of life in some cirrhotic patient populations. TIPSS is clinically effective: versus endoscopic band ligation (EBL) in second line treatment of variceal bleeding; and versus large volume paracentesis (LVP) in refractory ascites. However, there is a sparsity of UK based economic evidence determining the cost-effectiveness of TIPSS for these two indications. This study aimed to establish the cost-effectiveness of (i) TIPSS versus EBL in second line treatment of variceal bleeding, and (ii) TIPSS versus LVP in the management of refractory ascites. Methods: A cost-utility analysis was conducted from a UK health perspective including NHS costs and quality adjusted life years (QALYs). A Markov model was constructed which included health states for survival either with or without complications of liver cirrhosis including variceal bleeding, ascites and hepatic encephalopathy. The model was conducted across a 2-year time horizon and applied costs and dis-utilities per complication for each monthly cycle. Uncertainty was analysed in one-way deterministic and probabilistic sensitivity analyses. Results: TIPSS with the GORE® VIATORR® stent was cost-effective (dominant) and highly cost saving to the NHS for both populations. For the variceal bleeding indication, when compared with EBL, TIPSS resulted in 0.22 additional QALYs, saved the NHS £1, 301 per patient and had a 68% probability of being cost-effective. For the refractory ascites indication, when compared with LVP, TIPSS resulted in 0.526 additional QALYs, saved the NHS £17, 983 per patient and had a 100% probability of being cost-effective. Conclusions: TIPSS using a GORE® VIATORR® stent to manage patients with severe cirrhosis and RA or bleeding is expected to be cost-saving and improve patient outcomes. While TIPSS remains cost-saving and cost-effective in our base-case analysis for the management of high quality and adequately powered RCTs which also evaluate quality of life and health economics are required to inform robust economic analysis; mainly for the bleeding indication. Increased implementation of TIPSS is likely to improve patient outcomes and be cost saving to the NHS, particularly for the management of ascites.